Mobilità turistiche fuori dai luoghi. Forme e signiﬁcati dei viaggi online per i giovani italiani - Monaco, Salvatore (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2018)
In the “new mobilities” society (Urry, Sheller, 2006) until a few years ago unimaginable tourism experiences are realized. Nowadays the advent of new technologies makes possible also to travel without actually traveling, allowing tourists to move within unprecedented spatialities, in-betweeness (Rojek, Urry, 1997). Virtual and imaginative travels are the subject of this paper: their forms and meanings are analyzed starting from the results of anexploratory research carried out among a group of Italian millennials. The study highlights how this new form of tourism is a further element available to travelers in order to enrich, forge and shape their own identities. The ﬁnding of the study points out the overcoming of the anthropological proposal of place,which traditionally locates cultures in a physical (de)ﬁnite space (Hall, 1995).